2022
DOI: 10.1155/2022/7588680
|View full text |Cite|
|
Sign up to set email alerts
|

Image Effect Observation of Acanthopanax senticosus on Antifatigue Activity after Exercise

Abstract: In order to explore the effect of Acanthopanax senticosus on antifatigue activity after exercise, this paper proposes an image effect observation based on the effect of Acanthopanax senticosus on antifatigue activity after exercise. This method recommends key technical problems and solutions based on the information represented by image effect observation and explores the influence of Acanthopanax senticosus on antifatigue after exercise. Through the retrospective analysis of certain personnel, it is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The studies have shown that sleep deprivation causes excessive oxidation of free radicals in brain tissue, leading to degenerative changes in tissues and cells, making excessive lipofuscin and malondialdehyde (MDA), thus damaging brain function and reducing learning and memory capacity. In this study, ESF has been proved to significantly improve the above symptoms and counter the effects of chronic sleep deprivation on the central nervous system (Zhang & Zhu, 2022 ). The main components of ESF volatile oil and fatty oil were terpene and fatty acid compounds by GC–MS analysis.…”
Section: Resultsmentioning
confidence: 97%
“…The studies have shown that sleep deprivation causes excessive oxidation of free radicals in brain tissue, leading to degenerative changes in tissues and cells, making excessive lipofuscin and malondialdehyde (MDA), thus damaging brain function and reducing learning and memory capacity. In this study, ESF has been proved to significantly improve the above symptoms and counter the effects of chronic sleep deprivation on the central nervous system (Zhang & Zhu, 2022 ). The main components of ESF volatile oil and fatty oil were terpene and fatty acid compounds by GC–MS analysis.…”
Section: Resultsmentioning
confidence: 97%
“…E. sessiliflorus is a traditional tonic Chinese herbal medicine from the Changbai Mountain region of China, with mild medicinal properties, low toxicity, and antioxidant, anti-aging, and anti-fatigue properties ( Li et al, 2016 ; Jia et al, 2021 ; Li et al, 2022 ; Zhang and Zhu, 2022 ). E. sessiliflorus is rich in a variety of active ingredients, such as plant proteins, peptides, and polysaccharides, all of which have potent and strong antioxidant activity and hold promise for antioxidant drug development.…”
Section: Discussionmentioning
confidence: 99%
“…AS is a medicinal plant in the family of Araliaceae. Previous studies have shown that the active ingredients of AS can significantly improve blood lipid levels and endothelial cell function in patients with acute cerebral infarction, promote the proliferation of neural stem cells in ischemic brain tissue and have therapeutic effects on cerebrovascular diseases such as hypertension and cerebral infarction [18][19][20]. In addition, AS has a sedative effect on the central nervous system, which can improve anxiety, irritability, insomnia, and other symptoms, and is commonly used clinically for the treatment of abnormal affective disorders and neurological disorders [21][22].…”
Section: Discussionmentioning
confidence: 99%